Quarteto para contrabaixos 1995 de Ernst Mahle: análise interpretativa - Luna, Iradi Tavares de (2013)
This dissertation proposes an interpretative and formal analyses of Ernst Mahle‟s Quarteto 1995 for double-basses , with the purpose to learn better ways to perform this piece. We did a bibliografic study in which we elucidate part of Mahle‟s trajectory as an educator, some of his theoretical handouts as well as his key compositions for double bass in order to lead performers to a better understanding of the thematic, formal, motivic and modal aspects present in the Quarteto 1995 .